Analisis Hubungan Shift Kerja, Masa Kerja, Usia dan Kualitas Tidur terhadap Kelelahan Kerja (Fatigue) pada Pengemudi JakLingko Koperasi Jasa Angkutan Purimas Jaya - Melda Ayu Regiana; Santika Sari; Nur Fajriah (Journal of Optimization System and Ergonomy Implementation, 2023)
Fatigue is an important factor in ergonomics because it can affect the work ability of human resources. The term work fatigue leads to the condition of workers who are weakened to complete their work, resulting in a decrease in work capacity, endurance and work productivity. Work fatigue that occurs needs to be given special attention by the company in order to avoid hazards and risks that endanger workers and ongoing operational activities. One activity that has hazards and risks is driving. Driving fatigue is one of the factors causing accidents in the transportation sector so that it provides a high mortality rate. Therefore, this research was conducted at Mikrotrans JakLingko Koperasi Purimas Jaya to analyze the factors of work shifts, tenure, age and sleep quality that cause fatigue using the Subjective Self Rating Test method from the IFRC. The results showed that work shifts and fatigue had a value of 0.043 < 0.05, tenure and fatigue 0.874 > 0.05, age and fatigue 0.071 > 0.05 and sleep quality and fatigue 0.150 > 0.05. It is concluded that work shift and fatigue have a significant relationship. Meanwhile, tenure, age and sleep quality have no relationship to fatigue.